Evidence Base within Clinical Practice In Modern Medicine (A Clinicians Perspective) - Cobb, William James (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The aim of this work is to critically assess to what extent and in what ways evidence based practice may, or indeed may not, assist clinical practitioners to avoid confusing personal opinion with evidence. “We become confident in our educated guesswork to the point where it is easy to confuse personal opinion with evidence or personal ignorance with genuine scientific uncertainty” (Naylor 1995). The author of this work is a clinician currently practising in the area of acute and emergency and trauma healthcare, and therefore clinical treatments will be considered in the context of evidence based practice. This work has been formulated around an online postgraduate Master’s module investigating the meaning of evidence based practice in the modern healthcare setting. Some of the content of this work will draw upon the learning objectives of the evidence based module by using examples of online forum discussions, which took place during the module between various clinical practitioners. It is a further expectation of this work to examine to what extent and in what ways evidence based practice assists clinicians in making research based clinical decisions, whilst considering how evidence is or indeed is not amalgamated into clinical practice. Evidence and the concepts used to cement evidence into practice will be explored both by considering the online forum discussions that took place during the module, and again by looking at current research and literature to draw comparisons and extract ideas.